2015
DOI: 10.1002/ange.201500292
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Discriminating Termination of Chiral Supramolecular Polymerization: Tuning the Length of Nanofibers

Abstract: Directing the supramolecular polymerization towards ap referred type of organization is extremely important in the design of functional soft materials.Proposed herein is asimple methodology to tune the length and optical chirality of supramolecular polymers formed from ac hiral bichromophoric binaphthalene by the control of enantiomeric excess (ee). The enantiopure compound gave thin fibers longer than afew microns,while the racemic mixture favored the formation of nanoparticles.T he thermodynamic study unveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 59 publications
(35 reference statements)
2
25
0
Order By: Relevance
“…21) 32,[47][48][49][50][51] . Furthermore, we confirmed that the polymers of 1•2 S and 1•2 R were also immiscible [28][29][30][31][32] , which was proved by the linear change of CD intensity with changing the ratio of 1•2 S and of 1•2 R in their mixture (1•2 S :1•2 R = 100:0-0:100; Supplementary Fig. 22a), together with the fact that the elongation temperatures of enantiopure samples (1•2 S :1•2 R = 100:0 and 1•2 S :1•2 R = 0:100; T e = 335 K for both) were notably higher than that of a racemic sample (1•2 S :1•2 R = 50:50; T e = 315 K) ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…21) 32,[47][48][49][50][51] . Furthermore, we confirmed that the polymers of 1•2 S and 1•2 R were also immiscible [28][29][30][31][32] , which was proved by the linear change of CD intensity with changing the ratio of 1•2 S and of 1•2 R in their mixture (1•2 S :1•2 R = 100:0-0:100; Supplementary Fig. 22a), together with the fact that the elongation temperatures of enantiopure samples (1•2 S :1•2 R = 100:0 and 1•2 S :1•2 R = 0:100; T e = 335 K for both) were notably higher than that of a racemic sample (1•2 S :1•2 R = 50:50; T e = 315 K) ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 73%
“…The key to this achievement is our strategy of using the non-covalent interaction sites in the supramolecular polymer not only for the connection of the monomers but also for the recognition of chiral guests. that similar enantio-separation ability should reside in all reported supramolecular polymers that are formed via homochiral polymerization [28][29][30][31][32] , but has never been investigated. Speaking not only chirality recognition but general molecular recognition, all supramolecular polymers with self-sorting nature also potentially have the similar separation ability [47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The latter are of widespread importance as means of accessing polymers with chain length control, narrow length dispersities, and also complex architectures such as block and star copolymers. 1,[11][12][13][14][15][16][17][18] Crystallization is also a nucleation-elongation/growth process 19 and the solution self-assembly of block copolymers (BCPs) with a crystallizable core-forming block has received…”
mentioning
confidence: 99%
“…Instead, it is regulated by how the molecules are arranged in the self-assembled aggregates. Although various types of gelators have been shown to possess supramolecular chirality 23 24 25 26 , to date, very few peptide-based systems have been reported. For example, opposite supramolecular chirality (left- and right-handed) from porphyrin-conjugated pentapeptides in two different solvent systems were investigated by Jiang et al 27 .…”
mentioning
confidence: 99%